2012
DOI: 10.1007/s10552-012-9942-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of colorectal adenoma with components of metabolic syndrome

Abstract: Central obesity, triglyceride level, and MS are risk factors for colorectal adenoma including advanced adenoma and multiplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 33 publications
4
84
0
3
Order By: Relevance
“…A more recent case–control study comparing 1771 patients with diagnosed adenomas and 4667 polyp-free controls confirmed that a greater waist circumference was significantly associated with increased CRA risk (OR=1.32, 1.17 to 1.49) 37. In addition, MS was significantly associated with finding adenomas (OR=1.44, 1.23 to 1.70), regardless of histological type, CRA number or location other than rectum 37…”
Section: Resultsmentioning
confidence: 96%
“…A more recent case–control study comparing 1771 patients with diagnosed adenomas and 4667 polyp-free controls confirmed that a greater waist circumference was significantly associated with increased CRA risk (OR=1.32, 1.17 to 1.49) 37. In addition, MS was significantly associated with finding adenomas (OR=1.44, 1.23 to 1.70), regardless of histological type, CRA number or location other than rectum 37…”
Section: Resultsmentioning
confidence: 96%
“…However, the standard protocol recommends that screening is initiated after the age of 50 years. Previous studies have suggested that there is a certain degree of correlation between metabolic syndrome and colorectal adenoma, a precancerous lesion of CRC (12)(13)(14), our study aimed to develop a risk determinant for younger patients who may benefit from screening on the basis of their metabolic profiles and associated clinical history. The general adenoma detection rate of 20% for both sexes, 23% in males and 17% in females, is in line with standard quality indicators in colonoscopic practice (15).…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were fourteen studies on HDL-C (four cohort studies, four cross-sectional and six case-control studies) and risk of CRA published between 1990 and 2013 and involved a total of 14 098 CRA cases (Table 2) (6,9,10,(18)(19)(20)23,(26)(27)(28)(29)(30)(31)39) . Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%